(untitled) (Archive of Conferences, 2021)
The article analyzes the influence of mineral fertilizers on the growth period of camelina varieties. An increase in the rate of application of phosphorus fertilizers for autumn varieties of camelina up to 30 kg/ha led to an extension of the growing season of plants by 2- 3 days. An increase in the amount of nitrogen fertilization for every 30 kg/ha lengthens the growth period by 1-2 days. It was noted that an increase in the rate of potash fertilizers did not affect the period of plant growth.